Prevalence and Clinical Outcomes of Orbital Complications in Patients with Acute and Chronic Rhinosinusitis with Emphasis on Systemic Comorbidities. A Cross-Sectional Study - Chaudhry Muhammad Tariq Munawar, Rehan Moinuddin Shaikh, Javed Iqbal, Ahsan Qureshi, Mohammad Aamir Khan, Wing Commander Muhammad Tahir Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Orbital complications of rhinosinusitis are life threatening and vision threatening, in particular in patients with systemic comorbidities like diabetes mellitus and immunosuppression. These complications are caused by anatomical closeness between the paranasal sinuses and the orbit and can go as far as to cause life-threatening conditions such as cavernous sinus thrombosis. Objectives: The aim of the study was to evaluate the prevalence, pattern, and clinical outcomes of orbital complications in patients with acute and chronic rhinosinusitis with particular attention to the role of systemic comorbidities. Methods: A cross-sectional study was carried out between January 2022 and February 2023 at CMH Kharian Cantt and Sughra Shafi Medical Complex, Narowal. Eighty patients with clinically and radiologically proven orbital complications secondary to rhinosinusitis were included. Clinical assessments, imaging reports (CT/MRI) and laboratory tests were done. Outcomes were assessed including the need of surgery, stay in the hospital and visual impairment and the systemic comorbidities were recorded. Results: Preseptal cellulitis (37.5) and orbital cellulitis (28.8) were the most common. More severe complications such as orbital abscess (11.3%) and cavernous sinus thrombosis (5%) were more common in the patients with comorbidities. The most common comorbidity was diabetes mellitus (27.5%). Forty-five percent of the cases required surgical intervention and all the cases of permanent vision loss were among patients with systemic diseases. The length of hospitalization was much longer among patients with comorbidity (p = 0.002). Conclusion: Systemic comorbidities significantly worsen the severity and outcomes of orbital complications in rhinosinusitis. Early diagnosis and aggressive multidisciplinary management are crucial, especially in high-risk patients, to prevent irreversible complications. Keywords: Rhinosinusitis, Orbital complications, Preseptal cellulitis, Diabetes mellitus, Immunosuppression, Visual impairment, Surgical intervention.